2016
DOI: 10.3892/mco.2016.916
|View full text |Cite
|
Sign up to set email alerts
|

Quick regression of brain metastases from lung adenocarcinoma with epidermal growth factor receptor-tyrosine kinase inhibitor treatment: A case report and literature review

Abstract: Abstract. Brain metastasis (BM) commonly occurs in patients with advanced lung cancer, and is associated with poor prognosis and limited treatment options, particularly for end-stage patients who are in poor physical and mental state. We herein present a case of lung adenocarcinoma with BM, as revealed by tumor marker and imaging studies. The patient was a 74-year-old woman who was diagnosed with lung adenocarcinoma with several metastatic lesions in the mediastinal lymph nodes, bone and brain. The patient und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The reason for this low incidence rate might be that many patients have died from the primary tumor and complications before they developed BM. The majority of NSCLC patients who developed BM survive for 3–6 months, and the 1-year survival rate is 10% 14 . A study showed that the median progression-free survival (PFS) and OS were better in patients with common EGFR mutations than in patients with uncommon mutations (15.5 vs. 3.9 months, P < 0.001; and 37.3 vs. 17.4 months, P < 0.001; respectively) 7 .…”
Section: Discussionmentioning
confidence: 99%
“…The reason for this low incidence rate might be that many patients have died from the primary tumor and complications before they developed BM. The majority of NSCLC patients who developed BM survive for 3–6 months, and the 1-year survival rate is 10% 14 . A study showed that the median progression-free survival (PFS) and OS were better in patients with common EGFR mutations than in patients with uncommon mutations (15.5 vs. 3.9 months, P < 0.001; and 37.3 vs. 17.4 months, P < 0.001; respectively) 7 .…”
Section: Discussionmentioning
confidence: 99%